If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-6x + 1) = -329 Reorder the terms: 7(1 + -6x) = -329 (1 * 7 + -6x * 7) = -329 (7 + -42x) = -329 Solving 7 + -42x = -329 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -42x = -329 + -7 Combine like terms: 7 + -7 = 0 0 + -42x = -329 + -7 -42x = -329 + -7 Combine like terms: -329 + -7 = -336 -42x = -336 Divide each side by '-42'. x = 8 Simplifying x = 8
| X-2(x+3)=-2(x+1)-4 | | 2x+1+3x=30 | | x=a(a-b)+b(a+b) | | x=-3+13 | | 2x-3+19=17 | | 5x=63.25 | | [2x+3]=-5 | | 7(-1x+5)=-7 | | x^2-2+3x+8=180 | | -8y=48-4y | | 7.1x+4.4-2x-8.7= | | -7(2x+4)=-70 | | [8x+5]=21 | | 72-10x=12 | | -6x+2=3x-79 | | [4x-8]=20 | | x+4=-20-x | | 6x-3=-7x-133 | | 4-3x+2x=-18+2 | | 6=16-13d | | -140=4x-6(-x+10) | | 5y=-2x-15 | | 10x^2-42x+44=0 | | 5x+13=35+7x | | -1-2x-6x=-65 | | 5x-4=30x+16 | | 6x-4(2-x)=14 | | -17=-2x-2x-5 | | 2=8x-32 | | 4(5x-4)+4=-10 | | -4=3x+7(-x-4) | | 15x+10=8x+38 |